Simultaneous single-pulse observations of radio pulsars - IV. Flux density spectra of individual pulses - Kramer, M; Karastergiou, A; Gupta, Y; Johnston, S; Bhat, N; Lyne, A (2003)
In this paper we demonstrate that a large, unexplored reservoir of information about pulsar emission exists, that is directly linked to the radiating particles and their radiation process: We present a study of flux density measurements of individual pulses simultaneously observed at four different frequencies. Correcting for effects caused by the interstellar medium, we derive intrinsic flux density spectra of individual radio pulses observed at several frequencies for the first time. Pulsar B0329+54 was observed at 238, 626, 1412 and 4850 MHz, while observations of PSR B1133+16 were made at 341, 626, 1412 and 4850 MHz. We derive intrinsic pulse-to-pulse modulation indices which show a minimum around 1 GHz. Correlations between the flux densities of different frequency pairs worsen as the frequency separation widens and also tend to be worse for outer profile components. The single pulse spectra of PSR B0329+54 resemble the spectra of the integrated profile. However, the spectral index distributions for the single pulses of PSR B1133+16 show significant deviations from a Gaussian. This asymmetry is caused by very strong pulses with flux densities exceeding the mean value by more than a factor of ten. These strong pulses occur preferentially at the trailing edge of the leading component and appear to be broadband in most cases. Their properties are similar to those of so-called giant pulses, suggesting that these phenomena are related.